2022
DOI: 10.3390/vetsci9030146
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Bovine Viral Diarrhea Virus Infections in Pigs on Jeju Island, South Korea, from 2009–2019 and Experimental Infection of Pigs with BVDV Strains Isolated from Cattle

Abstract: On Jeju Island, South Korea, pigs have not been vaccinated against classical swine fever (CSF) since 1999. Analysis of bovine viral diarrhea virus (BVDV) isolated from pigs on Jeju Island between 2009 and 2019 identified five BVDV-1a strains and one BVDV-1b strain. These BVDV types were shown to be the same types as BVDV strains isolated from neighboring cow farms. BVDV antibody-positive pigs (both BVDV-1 and -2) were also detected at 54 of 168 pig farms during this period. In pig infection experiments using B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
(40 reference statements)
0
3
0
Order By: Relevance
“…Preliminary study 1 revealed the potential to detect BVDV and PCMV in OMM (Table 1). Cattle are BVDV's natural host; however, the prevalence of BVDV in commercial pig herds has been demonstrated to varying degrees (20). A low risk of transferring BVDV to bovine SCNT embryos was previously shown but not examined in swine (13).…”
Section: Discussionmentioning
confidence: 99%
“…Preliminary study 1 revealed the potential to detect BVDV and PCMV in OMM (Table 1). Cattle are BVDV's natural host; however, the prevalence of BVDV in commercial pig herds has been demonstrated to varying degrees (20). A low risk of transferring BVDV to bovine SCNT embryos was previously shown but not examined in swine (13).…”
Section: Discussionmentioning
confidence: 99%
“…For some of these pathogens, intraspecies transmission is still the subject of debate in the scientific community [1]. Examples of typical ruminant infections to which pigs are susceptible are Q fever, Schmallenberg virus (SBV), and bovine viral diarrhea (BVD) [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…Due to its genomic similarities with classical swine fever virus (CSFV; both are pestiviruses), the virus can also infect pigs [12]. BVD has been described in numerous reports in both pigs and wild boars, and scientific evidence has demonstrated seroconversion and viral shedding with various body fluids after experimental infection [4,[13][14][15]. Further studies have highlighted the absence of persistent and transplacental infections in pigs [16][17][18].…”
Section: Introductionmentioning
confidence: 99%